Analisis Industri Bisnis Jasa Online Ride Sharing di Indonesia - Berto Mulia Wibawa; Yani Rahmawati; Mathias Rainaldo (Esensi: Jurnal Bisnis dan Manajemen, 2018)
Analysis of Online Ride Sharing Business Industry in IndonesiaInnovation in transportation sector with sharing economy principal has create new service sector which is named online ride sharing service. There are a lot of online ride-sharing service players in Indonesia such as Go-Jek, Grab, and Uber. Nowadays, government also have rules on changing the condition of online ride-sharing. Therefore, industry analysis is needed to be analyze further to know the industry attractiveness of the online-ride sharing service. This study aims to analyze the level of attractiveness in online ride-sharing industry in Indonesia. This study used descriptive-explorative method on identifying Porter’s Five Forces as tools in industry analysis. Data collection is using ghost interview method to the selected driver. The conclusion is online-ride sharing industry in Indonesia is quite attractive to be developed in the future because the number of customers has not reached the maximum point, moreover the industry may offer a very diverse product differentiationDOI: 10.15408/ess.v8i1.5739